2002
DOI: 10.1034/j.1399-6576.2003.470106.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the catheter‐technique psoas compartment block and the epidural block for analgesia in partial hip replacement surgery

Abstract: The continuous psoas compartment block provides excellent intraoperative and postoperative analgesia with a low incidence of complications for partial hip replacement surgery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(41 citation statements)
references
References 21 publications
4
36
1
Order By: Relevance
“…Most patients of both groups were discharged in the third postoperative day and almost all patients of the sample were discharged before the fourth postoperative day. Our results are different from studies suggesting that cLPB speeds postoperative recovery 8,13 , suggesting that recovery times are similar for both groups. Reports of severe complications and familiarity with other techniques may explain the reluctance of anesthesiologists in choosing LPB.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Most patients of both groups were discharged in the third postoperative day and almost all patients of the sample were discharged before the fourth postoperative day. Our results are different from studies suggesting that cLPB speeds postoperative recovery 8,13 , suggesting that recovery times are similar for both groups. Reports of severe complications and familiarity with other techniques may explain the reluctance of anesthesiologists in choosing LPB.…”
Section: Discussioncontrasting
confidence: 56%
“…Results also suggest that adopted analgesia regimens are adequate for the postoperative period of patients submitted to hip arthroplasty. Scarce literature data report that LPB provides excellent intra and postoperative analgesia, decreases opioid consumption, speeds recovery and has few adverse effects 5,7,8 . Türker et al 8 have compared LPB and epidural analgesia and have not found statistically significant differences in pain intensity and postoperative rescue analgesia consumption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 1 (5%) RCT 15 was assessed as low risk of bias, 9 (43%) 14,[16][17][18][19][20][21][22][23] had high risk of bias, and the remaining 11 (52%) 13,[24][25][26][27][28][29][30][31][32][33] The Table lists key characteristics of the eligible studies. They were published from 1991 to 2010 and ranged in size from 14-209 participants.…”
Section: Resultsmentioning
confidence: 99%
“…We were able to compare acute pain intensity between seven nerve block strategies using data from 16 studies comprising 1,089 subjects. In 15 studies, pain was measured on a 10-cm visual analogue scale or an 11-point numeric rating scale, 13,16,17,[20][21][22][23][24][25]27,28,[30][31][32][33] and in one study, a four-point verbal rating scale was used. 18 Pain was also measured at a variety of intervals (ranging from hourly to daily).…”
Section: Resultsmentioning
confidence: 99%